(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
This article talks about the importance of gender equality in the process of upbringing in a family environment. The relationships of parents to each other, the principle of imitation in them, directly and indirectly influence the upbringing of the individual.